Construction and Practice of an Industry-Education Integration Curriculum System for Vocational Rehabilitation Therapy Technology Based on the ERAS Concept — Evaluation of Clinical Internship Teaching Effectiveness - Tian Zhu; Xianting Ju; Zidi Guo; Futian Ren; Yumeng Zhao (Journal of Artificial Intelligence and Information, 2026)
Accelerated Recovery After Surgery (ERAS) refers to a multidisciplinary collaborative approach centered around the perioperative period. While some hospitals in China have already implemented ERAS, it has not yet been introduced into the teaching or internship programs of higher vocational rehabilitation therapy technology majors. Currently, vocational rehabilitation programs face limited progress in industry-education collaboration, with few jointly developed courses by schools and enterprises, and insufficiently diverse evaluation methods for internships. From the perspective of industry-education integration, this paper introduces the ERAS concept into clinical internships for the rehabilitation therapy technology major, transforming issues based on the logic of “clinical pathway competency-based curriculum content.” Leveraging collaborations with top-tier tertiary hospitals, the curriculum is designed accordingly. The involved topics gather extensive literature resources based on practical needs, employing tools such as the Delphi method, action research, and quasi-experiments to analyze teaching practices, aiming to establish an evaluation model for vocational internships. According to the research conclusion, if the content described in ERAS is applied to courses or internships that combine industry and education, it can effectively fill the knowledge gap related to perioperative and interdisciplinary collaboration, make internship evaluation more effective, and cultivate talents that are more in line with job requirements, which has practical significance for vocational rehabilitation education.